2021
DOI: 10.1002/edn3.272
|View full text |Cite
|
Sign up to set email alerts
|

Density‐independent prey choice, taxonomy, life history, and web characteristics determine the diet and biocontrol potential of spiders (Linyphiidae and Lycosidae) in cereal crops

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 127 publications
(151 reference statements)
0
33
0
Order By: Relevance
“…Despite evidence existing for the biocontrol potential of many other web‐building spiders (Chapman et al, 2013; Cuff et al, 2021; Vink & Kean, 2013), Michalko et al (2019) found in a global meta‐analysis that web‐building spiders have a poor, often negative effect on pest suppression. Many such spiders also negate their own biocontrol activity through high incidences of intraguild predation (Cuff, Tercel, et al, 2022; Hambäck et al, 2021; Petráková et al, 2016). Assumptions about the biocontrol efficacy of such spiders are thus contentious, so further research should focus on elucidating the trophic ecology of these spiders to ascertain how regular and effective their interactions with pests may be.…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence existing for the biocontrol potential of many other web‐building spiders (Chapman et al, 2013; Cuff et al, 2021; Vink & Kean, 2013), Michalko et al (2019) found in a global meta‐analysis that web‐building spiders have a poor, often negative effect on pest suppression. Many such spiders also negate their own biocontrol activity through high incidences of intraguild predation (Cuff, Tercel, et al, 2022; Hambäck et al, 2021; Petráková et al, 2016). Assumptions about the biocontrol efficacy of such spiders are thus contentious, so further research should focus on elucidating the trophic ecology of these spiders to ascertain how regular and effective their interactions with pests may be.…”
Section: Discussionmentioning
confidence: 99%
“…This facilitates often non‐invasive detection of a greater dietary diversity than traditional techniques such as hard‐part analysis, even in vertebrate consumers (Jeanniard‐du‐Dot et al., 2017). Even greater, however, is the advance in access to invertebrate dietary information through DNA‐based methods, since most traditional methods are not applicable to the minute gut contents or faeces of invertebrates, especially fluid feeders (Cuff, Tercel, et al., 2021; Cuff, Drake, et al., 2021; Lafage et al., 2019; Pompanon et al., 2012; Symondson, 2002). Since the advent of high‐throughput sequencing, ‘DNA metabarcoding’, the parallel identification of many species using short DNA amplicons, has become an increasingly common and accurate method for the identification of species consumed by a given animal (Clare, 2014; Pompanon et al., 2012).…”
Section: The Value Of Dietary Dna Metabarcoding For Network Ecologymentioning
confidence: 99%
“…However, dietary metabarcoding does theoretically facilitate the merging of complex multilayer networks including many types of interactions across multiple trophic levels, including interactions within trophic levels (i.e. intra‐guild predation; Cuff, Tercel, et al 2021; Hambäck et al., 2021; Parimuchová et al., 2021; Saqib et al., 2021). The evolutionary data inherent to the output of metabarcoding also facilitates the incorporation of phylogenetic data into networks for enhanced evolutionary context and an improved understanding of how eco‐evolutionary processes affect important ecosystem functions such as pollination and parasitism (Derocles, Lunt, et al., 2018; Handley et al., 2011; Kitson et al., 2018; Melián et al., 2018; Segar et al., 2020).…”
Section: Examples Of Dna Metabarcoding In Networkmentioning
confidence: 99%
“…The choice of either attempting to silence or potentially being swamped by predator DNA is an insidious one given the financial, practical and experimental implications. The increased adoption of multiprimer (often multimarker, i.e., across multiple genes) metabarcoding (e.g., Batuecas et al, 2022; Cuff, Tercel, et al, 2022; da Silva et al, 2019, 2020; Stenhouse et al, 2021; Tercel et al, 2022) offers the option of using both approaches in synergy, but is by no means a panacea. Multimarker metabarcoding has been more generally suggested as a means of overcoming the issues associated with PCR primer bias (Browett et al, 2021; Cuff, Windsor, et al, 2022; da Silva et al, 2019).…”
Section: Comparing Common Strategies For Overcoming the Predator Problemmentioning
confidence: 99%